2011
DOI: 10.1007/s00894-011-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

The H2 dissociation on the BN, AlN, BP and AlP nanotubes: a comparative study

Abstract: The thermodynamic and kinetic feasibility of H(2) dissociation on the BN, AlN, BP and AlP zigzag nanotubes has been investigated theoretically by calculating the dissociation and activation energies. We determined the BN and AlP tubes to be inert toward H(2) dissociation, both thermodynamically and kinetically. The reactions are endothermic by 5.8 and 3 kcal mol(-1), exhibiting high activation energies of 38.8 and 30.6 kcal mol(-1), respectively. Our results indicated that H(2) dissociation is thermodynamicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Geometry optimizations, energy calculations, and density of states (DOS) analysis were performed on the BeONT and different H 2 CO/BeONT complexes using B3LYP functional augmented with an empirical dispersion term (B3LYP-D [18]) with 6-31G (d) basis set as implemented in GAMESS suite of programs [19]. The B3LYP is demonstrated to be a reliable and commonly used level of theory in the study of different nanostructures [20][21][22][23][24][25][26][27]. It has been previously shown t 6-31G(d) is an optimal basis set from the standpoints of calculation time and accuracy for B3LYP functional among four 6-31G, 6-31G(d), 6-31+G(d), and 6-31++G(d, p) basis sets [28].…”
Section: Methodsmentioning
confidence: 99%
“…Geometry optimizations, energy calculations, and density of states (DOS) analysis were performed on the BeONT and different H 2 CO/BeONT complexes using B3LYP functional augmented with an empirical dispersion term (B3LYP-D [18]) with 6-31G (d) basis set as implemented in GAMESS suite of programs [19]. The B3LYP is demonstrated to be a reliable and commonly used level of theory in the study of different nanostructures [20][21][22][23][24][25][26][27]. It has been previously shown t 6-31G(d) is an optimal basis set from the standpoints of calculation time and accuracy for B3LYP functional among four 6-31G, 6-31G(d), 6-31+G(d), and 6-31++G(d, p) basis sets [28].…”
Section: Methodsmentioning
confidence: 99%
“…But SWCNTs have some certain disadvantages which have encouraged scientists to think about modeling and synthesizing a substitute for it [18]. Several studies have been recently dedicated to the examination of various types of non-carbon nanotubes [19][20][21][22]. Numerous theoretical and experimental studies on stable tubular structures of the counterparts of groups III and V have been reported [10,23,24].…”
Section: Introductionmentioning
confidence: 97%
“…[56][57][58] The Gibbs free energy of process of adsorption of halogen atom (X = F, Cl, Br) on studied nanostructures were calculated via: G ad = G (X-nanostructure) -G (nanostructure) -0.5 G (X 2 ), where X-nanostructure corresponds to the Gibbs free energy of complexes of nanostructure with halogen atom, G (X 2 ) is the Gibbs free energy of the halogen molecule and G (nanostructure) is the Gibbs free energy of the nanostructure. [59][60][61] The Gibbs free energy of adsorption of metal on nanostructure surfaces were calculated via: G ad = G (M-nanostructure) -G (nanostructure) -G (M); where G (M-nanostructure) corresponds to the Gibbs free energy of complexes of nanostructure with metal and G (M) is the Gibbs free energy of the metal and G (nanostructure) is Gibbs free energy of the nanostructure. [62][63][64] In this study, the energies of the basis set superposition error (E BSSE ) for studied interactions between nanostructures and metals were calculated by using of counterpoise correction method and obtained results showed that E BSSE values are ca 0.05 Kcal/mol.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this section the effects of water as polar solvent on performance of C 38 , Si 19 Ge 19 , and their halogen-doped nanostructures as anode electrodes of metal-ion batteries via via DFT/ M06-2X theory, 6-311+G (2d, 2p) basis set and polarized continuum model (PCM) as solvent model were investigated. [56][57][58][59][60][61]…”
Section: Solvent Effects On Potential Of Studied Metal-ion Batteriesmentioning
confidence: 99%